Avaliação de diferentes aplicações do óleo essencial de Lippia sidoides em prótese dentária - Barreto, Joel Oliveira (2023)
The antimicrobial activity of an experimental solution containing Lippia sidoides essential oil (LSEO), its effect on physical-mechanical properties of a denture base acrylic resin, and the antimicrobial potential of an OELS-incorporated resilient denture reline were evaluated. The minimum inhibitory (MIC) and fungicidal/bactericidal (MFC/MBC) concentrations of the solution were determined against Candida albicans, Staphylococcus aureus and Pseudomona aeruginosa, as well as the effect on the metabolic activity of the C. albicans biofilm, through the XTT reduction method, in comparison to 1% sodium hypochlorite (NaOCl 1%) and 0.2% chlorhexidine digluconate (CHX 0.2%). Biofilm morphology was evaluated using Scanning Electron Microscopy (SEM). The solution showed good antimicrobial action against the tested pathogens (C. albicans - MIC and MFC: 19.53 µg/ml; S. aureus - MIC and MBC: 78.12 µg/ml; P. aerauginosa - MIC: 625 µg/ml and MBC: 2.500 µg/ml). After 20 minutes and 8 hours of immersion in the solutions with concentrations 10×(195.3 µg/mL) and 20×CFM (390.6 µg/mL), the metabolic activity of the biofilm was reduced by approximately 70% and 93%, respectively. Afterwards, acrylic resin specimens were divided into five groups according to the immersion solution: distilled water, 1% NaOCl, 0.2% CHX, 0.02% OELS solution (10xMFC), and 0.2% OELS solution (100xMFC). At baseline and after 15, 25 and 50 days of immersion, surface roughness, microhardness, color stability, mass, and flexural strength were evaluated. The surface of the material was evaluated by SEM. The OELS solutions generated controlled changes in roughness, microhardness and mass, similar to those caused by distilled water. At the 0.2% concentration, the change in color stability and the reduction in flexural strength resembled that of 1% NaOCl and 0.2% CHX, occurring, however, within the limits of clinical acceptability and maintenance of material strength. Finally, specimens of a temporary resilient material were divided into four groups according to the antimicrobial agent incorporated: 1 – no antimicrobial agent added; 2 and 3 - OELS at concentrations of 0.01g/mL (1%) and 0.02g/mL (2%), respectively (test groups); 4 - Nystatin 0.032g/mL. After the formation of multispecies biofilms of S. aureus, P. aeruginosa and C. albicans on the specimens, the microbial load of the microorganisms were evaluated by counting the number of colony forming units (CFU/mL), the metabolic activity of the mixed biofilm by reducing XTT, and the structure of the biofilm by identifying live and dead cells in Fluorescence Microscopy. At the 2% concentration, the incorporation of OELS significantly reduced the microbial load of S. aureus, biofilm formation, as well as its cell viability. It was concluded that the experimental solution containing OELS in concentrations above 195.3µg/mL has the potential to be used as a sanitizer for dental prostheses, without causing clinically relevant changes in the physical-mechanical properties tested. Moreover, the incorporation of OELS in a 2% concentration increases the antimicrobial activity of the resilient relining material against the evaluated microorganisms.